Soluble solids monitored in the clusters in minitomato hybrids from dwarf lines - Rafael Resende Finzi; Guilherme Repeza Marquez; Gabriel Mascarenhas Maciel; Maurício Pivetta Momesso; Lucas Medeiros Pereira; Aline José da Silveira (Agrarian, 2019)
On minitomatoes, the soluble solids content (SSC) is a fundamental characteristic for commercialization. During the productive cycle of the crop several harvests are realized, resulting in variations in the SSC from different genotypes. The objective of the experiment was to evaluate the genetic variability and to monitor SSC in the clusters of different minitomato hybrids from dwarf lines. The SSC of the fruits were evaluated according with their position of the clusters, being the values expressed in 0Brix. The genetic diversity was obtained by multivariate analyzes, using the generalized distance of Mahalanobis, utilizing different grouping methods (UPGMA and Tocher). The hybrids performance for SSC was checked by the Scott-Knott test (p=0.005). The cluster’s position influenced on the SSC of the minitomatoes fruits and the first cluster of all hybrids that were evaluated, presented the highest SSC. Besides that, the highest 0Brix variability among the genotypes occurred when the fruits were harvested on the fifth and first cluster. Most hybrids originated from dwarf lines did not presented a reduce on 0Brix values during the harvests.